Post-Disaster Recovery: Restoring Economic Growth through Urban Redevelopment - PERTIWI, WARDAH WULANDARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In this study I investigate how urban redevelopment can be a driver of economic growth after disaster. As urban redevelopment has many aspects, this study is narrowed down to physical entities and specified only to infrastructures. Two empirical evidences, Kobe Earthquake 1995 and Hurricane Katrina 2005, are being discussed in this paper. From two empirical evidences, it is found that the reconstruction of business infrastructures, public infrastructures, and housing have their respective roles to enhance economic growth after disaster. Furthermore, business infrastructures, public infrastructures, and housing have their different and unique ways to affect the regional economic growth.